Genicular Artery Embolization for Primary Knee Osteoarthritis - Tyagi, Ravi; Ahmed, S. Samaduddin; Koethe, Yilun; Raskind, Aleksandr; Ahmed, Osman (Seminars in Interventional Radiology, 2022)
Genicular artery embolization (GAE) is a novel treatment for knee osteoarthritis (OA) with increasing interest and utilization worldwide. The genicular arteries are selectively embolized using microspheres with subsequent cessation of abnormal synovial hyperemia, a process believed to arrest the inflammatory changes and pain associated with OA. Current data indicate that GAE offers sustained, 6-month improvement in Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) and visual analog scale scores in 80 to 85% of patients with mild to moderate OA. As GAE gains traction, future studies are needed to establish its safety and efficacy relative to placebo and other standard-of-care therapies while also characterizing populations for which it is most effective.
Keywords: GAE; genicular artery embolization; osteoarthritis; embolization; WOMAC; WORMS; VAS; interventional radiology